2016
DOI: 10.1155/2016/9139731
|View full text |Cite
|
Sign up to set email alerts
|

The Peroxidation of Leukocytes Index Ratio Reveals the Prooxidant Effect of Green Tea Extract

Abstract: Despite tea increased plasma nonenzymatic antioxidant capacity, the European Food Safety Administration (EFSA) denied claims related to tea and its protection from oxidative damage. Furthermore, the Supplement Information Expert Committee (DSI EC) expressed some doubts on the safety of green tea extract (GTE). We performed a pilot study in order to evaluate the effect of a single dose of two capsules of a GTE supplement (200 mg × 2) on the peroxidation of leukocytes index ratio (PLIR) in relation to uric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Tea polyphenols may exert antioxidant capacities through the following mechanisms: (1) straightly reducing oxidants; (2) chelating metal ions; (3) transferring hydrogen; (4) scavenging free radicals; (5) improving activities of antioxidant enzymes; (6) increasing contents of endogenous antioxidants; and (7) regulating antioxidant-related genes [4,44,45,46,47,48,49,50,51]. All of these actions lead to the health functions of tea, such as anticancer, cardiovascular protective, neuroprotective, hepatoprotective, and renoprotective effects [6,52,53,54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Tea polyphenols may exert antioxidant capacities through the following mechanisms: (1) straightly reducing oxidants; (2) chelating metal ions; (3) transferring hydrogen; (4) scavenging free radicals; (5) improving activities of antioxidant enzymes; (6) increasing contents of endogenous antioxidants; and (7) regulating antioxidant-related genes [4,44,45,46,47,48,49,50,51]. All of these actions lead to the health functions of tea, such as anticancer, cardiovascular protective, neuroprotective, hepatoprotective, and renoprotective effects [6,52,53,54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some studies have reported the antioxidant activity of tea brewing, extract and its components, which may have the potential for management of oxidative stress-induced diseases [80][81][82].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The antioxidant activity of tea brewing, extract and its components has been evaluated by several in vitro biological assay methods using cellular antioxidant activity (CAA), erythrocyte hemolysis, and plasma oxidation assays [80][81][82]. Zeng et al assessed the CAA of 27 tea cultivars, and the CAA values were 37.7-134.3 µmol quercetin equivalent (QE)/g dry weight (DW) (11.4-40.6 mg QE/g DW) without phosphate buffer washing, and 25.3-75.4 µmol QE/g DW (7.6-22.8 mg QE/g DW) with phosphate buffer washing [80].…”
Section: Antioxidant Activity In Vitromentioning
confidence: 99%